1997
DOI: 10.1159/000237625
|View full text |Cite
|
Sign up to set email alerts
|

Human IgE Binding Capacity of Tryptic Peptides from Bovine α-Lactalbumin

Abstract: The specific IgE binding capacity of native bovine α-lactalbumin (α-La), a globular whey protein, and tryptic peptides was investigated using 19 sera from patients with cow’s milk protein allergy. The specific anti-bovine α-La IgE titers ranged from 0.6 to 125 IU/ml. Highly purified tryptic peptides from native and disulfide-bond-reduced α-La were obtained by reverse phase chromatography. By ELISA technique using immobilized native protein or peptides, 11 of the 19 sera reacted exclusively with intact protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
0
2

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(54 citation statements)
references
References 16 publications
4
45
0
2
Order By: Relevance
“…A number of studies have suggested that peptide fragmentation generated from proteolytic digestion or hydrolysis of food allergens can elicit IgE responses in already sensitized individuals [14,15,16]. Maynard et al [14] showed that 8 out of 19 exhibited a specific IgE response to different tryptic peptides among the sera from patients with cow’s milk allergy.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have suggested that peptide fragmentation generated from proteolytic digestion or hydrolysis of food allergens can elicit IgE responses in already sensitized individuals [14,15,16]. Maynard et al [14] showed that 8 out of 19 exhibited a specific IgE response to different tryptic peptides among the sera from patients with cow’s milk allergy.…”
Section: Discussionmentioning
confidence: 99%
“…A protein could appear stable or unstable in SGF (or SIF), depending on the relative amounts of enzyme and test protein used Fu et al 2002). Some studies of effects of proteolytic digestion on allergenicity have used comparatively low ratios (by weight) of enzyme:protein, ranging from 0.1 to 0.01 (Asselin et al 1989;Marquez and Lajolo 1981;Maynard et al 1997;Watanabe et al 1990). However, in vitro digestion assays for the purposes of safety assessment tend to employ higher ratios ranging from 25 to 5,000 (Fu 2002;Fuchs et al 1993;Noteborn et al 1995;Reed et al 1996).…”
Section: Methodsmentioning
confidence: 99%
“…A study concerning the allergenic properties of α-La demonstrated that in 60% of the study patients, allergic sera were specific for intact α-La with only 40% binding to peptides obtained after tryptic hydrolysis. Residue 17-58 was the most frequently recognized in the sequence 59-93, 99-108, and 109-123 [79]. The linear epitopes were identified by using sera of patients suffering from persistent allergies and IgE to cow's milk levels > 100 kU(A)/L.…”
Section: β-Lgmentioning
confidence: 99%